Web-based Approach Bias Modification in smokers: A randomized-controlled study. (May 2019) - Wittekind, Charlotte E.; Lüdecke, Daniel; Cludius, Barbara
Abstract: Smoking is associated with automatic approach tendencies towards smoking-related stimuli. Therefore, it has been investigated whether training smoking individuals to consistently avoid smoking-related stimuli exerts positive effects on smoking behavior (Approach-Bias Modification [AppBM]). A web-based pilot study provided preliminary evidence for the effectiveness of AppBM in smokers; however, interpretability was constrained by several limitations. The aim of the present study was to replicate and extend previous findings. A web-based three group parallel (1:1:1) randomized-controlled study with adult smokers ( N  = 149) was conducted (DRKS00011901). Upon completion of a baseline assessment, participants were randomized to either six sessions of AppBM or Sham training or a waitlist control group. In both trainings, participants were presented smoking-related and neutral pictures. While all smoking-related pictures were associated with pushing and all neutral pictures with pulling in AppBM training, the contingency was 50:50 in Sham training. Participants were re-assessed directly and six months after training. Primary outcome was daily cigarette consumption at follow-up. At follow-up, no significant group differences emerged, although AppBM training significantly reduced daily cigarette consumption directly after training. No consistent change of bias through AppBM training emerged. This study does not provide support for the long-term effectiveness of AppBM training as a stand-alone training in smoking. Pre-registration: German Clinical Trials Register (DRKS00011901). Highlights: Web-based RCT to investigate short- and long-term effectiveness of AppBM. AppBM reduced daily cigarette consumption in the short, but not in the long-term. No effects on tobacco dependence and compulsive smoking behavior were found.